The Urgency of Understanding Parenting Science by Millennial Parents - Mardiani, Desika Putri (Jurnal Paradigma, 2023)
From year to year, the population is certain to increase. As time goes by, it is also accompanied by the development of science and technology that supports human life, including in the field of parenting science or more popularly referred to as parenting science. Various parties invite young parents, or we know the millennial generation, to be better at nurturing their children, especially early childhood. These young parents have wider access to parenting methods in an increasingly open era like today, they can learn many things through books that are sold freely, and also through online seminars or from various other sources of educational content. As said by Dr. Montessori, that the most important thing for millennial parents to realize is that children are part of a society that is still in the process of learning to understand what is in their environment. There are three important things that are the main needs of children in a parenting process, namely nutrition, stimulation and a sense of security. Nutrition is the first principal as a source of child growth in the form of food intake needed by children, stimulation as a process of stimulating maturity in every child's development, and a sense of security as a comfortable atmosphere for children and is a condition that is expected to occur in every child's activity. Parenting science is a form of parenting basic pattern and becomes flexible to be integrated with fields of science related to principles, value systems in society, beliefs, psychology, health, and various other scientific fields. Through the correct understanding of parenting, as well as proper emotional management, millennial parents will be able to live in the right parenting atmosphere, where they are able to present a comfortable family atmosphere, become a source of security for children, and form positive characters in children as their basis. grow into a dignified adult human. When they are adults, the provision of nutrition, stimulation and a sense of security will also be repeated to their children and their offspring in the future. That way, the majority of people who understand and apply parenting will form a society that has a positive character